Zdolności muzyczne dzieci - badania pilotażowe = Children`s musical abilities - Kuligowska, Emilia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents selected issues on the musical development of preschool children. A fragment of the Core Curriculum for kindergartens and other forms of preschool education concerning the content of education through art ? music was presented. The author described the research tool - Intermediate Measure of Music Audiation by Edwin E. Gordon (IMMA) and its use during the pilot study on five and six year old children.
Keywords: rozwój muzyczny; zdolności muzyczne; muzyka w przedszkolu; uzdolnienia; musical development of a child; musical abilities and interests of children; music in kindergarten; aptitudes